The Activation and Regulation of β2 Integrins in Phagocytes and Phagocytosis - Sun, Hao; Zhi, Kangkang; Hu, Liang; Fan, Zhichao (Frontiers in Immunology, 2021)
Phagocytes, which include neutrophils, monocytes, macrophages, and dendritic cells, protect the body by removing foreign particles, bacteria, and dead or dying cells. Phagocytic integrins are greatly involved in the recognition of and adhesion to specific antigens on cells and pathogens during phagocytosis as well as the recruitment of immune cells. β2 integrins, including αLβ2, αMβ2, αXβ2, and αDβ2, are the major integrins presented on the phagocyte surface. The activation of β2 integrins is essential to the recruitment and phagocytic function of these phagocytes and is critical for the regulation of inflammation and immune defense. However, aberrant activation of β2 integrins aggravates auto-immune diseases, such as psoriasis, arthritis, and multiple sclerosis, and facilitates tumor metastasis, making them double-edged swords as candidates for therapeutic intervention. Therefore, precise regulation of phagocyte activities by targeting β2 integrins should promote their host defense functions with minimal side effects on other cells. Here, we reviewed advances in the regulatory mechanisms underlying β2 integrin inside-out signaling, as well as the roles of β2 integrin activation in phagocyte functions.